Caesarean delivery on maternal request: need to redefine in view of intrapartum cases - Mahale, Anannya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Caesarean delivery on maternal request: need to redefine in view of intrapartum cases. The reasons are two-1) Recently I finished analysing indications for caesarean delivery at my institution for the period 01/04/2018 to 30/03/2019 (pre-COVID-19) as a part of my dissertation. 2) I also read articles from these and other authors related to Robson ten group classification system.